The Role of Coastal Upwelling in Suppressing the Warming Trend of Sea Surface Temperature along the Southern Coast of Java - Himawa, Daenk; Wirasatriya, Anindya; Kunarso, Kunarso; Wetchayont, Parichat (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
This study examines the unclear role of wind-driven upwelling through Ekman transport and pumping, along with the combined effects of the Indian Ocean Dipole (IOD) and El Niño-Southern Oscillation (ENSO) trends on the warming rate of Sea Surface Temperature (SST) along the southern coast of Java. Using data from 1940 to 2023, we investigated how IOD, ENSO, Ekman transport, and Ekman pumping influence SST trends. Our results reveal a cooling trend in SST near the coast during the upwelling period and a warming trend across the entire area during the non-upwelling period. The cooling SST weakens the easterly winds passing through the coastal areas, reducing upwelling intensity, as indicated by the weakening of Ekman transport. However, Ekman pumping, another proxy for upwelling, shows a strengthening trend. Our comparison along coastal areas suggests that the increase in Ekman pumping is more robust than the decrease in Ekman transport, leading to an overall intensification of upwelling. Additionally, we observed positive trends in IOD and ENSO during the upwelling period. These trends significantly enhance the upwelling process and are responsible for the observed cooling trend in SST. Thus, while wind-driven upwelling through Ekman transport and pumping plays a crucial role as a key process, its intensification is primarily driven by the trends in IOD and ENSO.